The legal seclusion of the imprisoned husband between Sharia and law - Ali, Professor Dr. Hamid Sultan; Muthana Ahmed Nuri (The college of law and political science journal, 2023)
Imprisonment of the husband is one of the matters that has an impact not on the husband who is sentenced to imprisonment, but rather extends its impact on the wife, as the damage affects everyone not only from the material side, but there is another and important aspect, which is the moral side in that the wife feels emptiness and fear from her husband’s distance from her.      The topic of our research is summed up that some of the wives do not want to separate from their husbands. Here the wife is oppressed because of the difficulty of meeting her husband in particular. Here the wife is confused about her matter, which leads her to demolish her family and ask for a divorce. Islamic Sharia in some of them, as Islamic Sharia dealt with the issues of the absence and distance of the husband in detail, unlike the Iraqi legislator, which specified few articles in this regard.